Cirrhosis and its Complication: other Clinical Complications Except ACLF and Critical Illness - Akram, Umair; Iqbal, Muhammad Faizan; Priya; Berkha; Rumela; Devi, Uma (Archives of Clinical and Biomedical Research, 2023)
Cirrhosis results from chronic liver disease, and is characterized by advanced fibrosis, scarring, and formation of regenerative nodules leading to architectural distortion. The main objective of the study is to find the cirrhosis and its complication, other clinical complications except ACLF and critical illness. This descriptive study was conducted at DHQ hospital, Vehari, Pakistan during June 2022 to January 2023. A comprehensive literature search of the published data was performed in regard with the spectrum, diagnosis, and management of cirrhosis and its complications. Data was also collected from OPD of the hospital record. We include all patients suffering from liver cirrhosis and its complication. It is concluded that patients with cirrhosis have progressive disease and suffer from multiple complications like ascites, HE, variceal bleeding, hepatorenal syndrome, cirrhotic cardiomyopathy, pulmonary syndromes, sarcopenia, frailty, and HCC. The prevention, early diagnosis, treatment, and palliation of these complications are essential in comprehensive clinical care plans.